A non-luminescent polymorph of [(cyclohexyl isocyanide)2Au]PF6 that becomes luminescent upon grinding or exposure to dichloromethane vapor. Issue 6 (23rd December 2020) - Luong, Lucy M. C.; Olmstead, Marilyn M.; Balch, Alan L.
Abstract : Colorless crystals of the new non-luminescent polymorph of [(C6 H11 NC)2 Au]PF6 (3 ) become luminescent upon grinding or exposure to dichloromethane vapour. Abstract : The discovery of a third, non-luminescent crystalline polymorph of [(C6 H11 NC)2 Au]PF6 is reported. Remarkably, crystals of this polymorph are sensitive to mechanical pressure or to exposure to dichloromethane vapor. In both cases, the conversion produces the yellow, green luminescent polymorph of [(C6 H11 NC)2 Au]PF6 and not the colorless, blue luminescent polymorph.